Control the Conversation : How to Claim, Deflect and Defend Your Position Through Any Line of Questioning - Karinch, Maryann (Career Press, 2018)
Where were you tonight? How did that meeting go? Are you seeing someone else? What qualifies you for this job? These are just a few of the usual questions we might answer in a day. A typical answer to the last question would include a series of "whats": what experience you have, what you studied in school, and what you do well. In Control the Conversation, the authors guide you in crafting a response to a question, not just an answer. A response should be multi-dimensional and include relevant and compelling information that goes beyond a mere answer.The authors help you build and apply this skill set. You will learn how to manage the four areas of disclosure--people, places, things, and events in time. You will also develop competence in techniques that will help you take control and get your message across in any kind of interview. You will discover how to:Master answer enhancers, such as keywords and body languageAnalyze a question and understand the motivation behind itUse questions artfully as part of your responseWith these skills as part of your repertoire, you'll also learn apply them in specific applications such as:Job interviewsSalesCommon exchangesMeetings and mediaDating and family situationsNo matter the question, Control the Conversation will show you how to steer every exchange in your favor.